1989
DOI: 10.1111/j.1528-1157.1989.tb05467.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicycling Movements as a Manifestation of Complex Partial Seizures of Temporal Lobe Origin

Abstract: Alternating movements of the limbs during a seizure, especially bicycling movements of the legs, are often taken as strong evidence for the psychogenic origin of seizure activity in an adult population. A recent review of pseudoseizure manifestations concluded that alternating limb movements were "highly characteristic of pseudoseizures." We report two adult patients with complex partial seizures of temporal lobe origin, confirmed by ictal video EEG recording, in whom bicycling movements were the prominent ict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Three preliminary reports have described similar behaviors occurring in the context of temporal lobe seizures. In one case, Sussman et al (1989) noted such behaviors after bilateral spread of discharges from a temporal lobe origin. In two other studies similar automatisms were noted in the course of temporal lobe seizures (Sussman e t al., 1989;.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three preliminary reports have described similar behaviors occurring in the context of temporal lobe seizures. In one case, Sussman et al (1989) noted such behaviors after bilateral spread of discharges from a temporal lobe origin. In two other studies similar automatisms were noted in the course of temporal lobe seizures (Sussman e t al., 1989;.…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators have described orbitofrontal or deep mesiofrontal seizures without BBAs (Penfield and Kristiansen, 1951;Bancaud et al, 1965, Niedermeyer andWalker, 1971). Of the three reports suggesting that these automatisms could appear in the course of temporal lobe seizures (Sussman et al, 1989;Park et al, 1990;, only the last two preliminary reports correlated location of discharges at time of occurrence of the automatisms in question, suggesting that bilateral spread had occurred at the time these BBAs appeared.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bicycling leg movements have also been reported in seizures originating from the temporal lobe. 55…”
mentioning
confidence: 99%
“…In particular, seizures arising from the frontal lobes proved to break most of the established assumptions. Hypermotor seizures (as they are termed by Azar et al in this report) associated with frontal lobe epilepsy commonly display all of the behaviors thought to be virtually diagnostic of pseudoseizures, while EEG/video of pseudoseizures has revealed that urination, injury, and drug responsiveness may be part of many nonepileptic episodes (2,3). As a result, EEG/video has become the gold standard for discriminating between epileptic and nonepileptic attacks.…”
Section: Commentarymentioning
confidence: 73%